RETRACTED: The Association of COVID-19 Pandemic Stress With Health-Related Quality of Life in the Kingdom of Saudi Arabia: A Cross-Sectional Analytical Study - Hawash, Manal Mohammed; Alhazmi, Amani Hamad; Wafik, Wagida; Muzammil, Khursheed; Mushfiq, Sakeena; Ahmed, Hala Awad (Frontiers in Public Health, 2021)
Background: There is a global disaster since WHO declared Covid-19 as a pandemic. With the increase in cases & mortality rate, various health issues viz., stress, mental disorders and altered health-related quality of life have been noted as a result of pandemic and lockdowns. This study aimed to assess the association of COVID-19 pandemic stress with health-related quality of life in the Kingdom of Saudi Arabia. Methodology: It was a cross-sectional analytical study. Subjects included 878 citizens and residents of Saudi Arabia aged 18 years and above. Convenience, non-probability sampling technique was used. A web-based, self-administered, electronic questionnaire in Arabic language having three sections; Sociodemographic & clinical profile, Standard PSS-10, and Standard SF-12 was used as the study tool and distributed through various social media means. The study period was of 2 months. Data were analyzed using SPS version 25. Descriptive statistics, Pearson's correlation coefficient, independent sample t-test and the one-way analysis of variance (ANOVA) were employed for suitable statistical analysis. Results: Almost two-thirds of the subjects were between the age of 18 to < 40 and majority (74.1%) being females. Majority (83.0%) reported as having no chronic diseases, and 69.5% had no contact history with COVID-19 cases. The mean of MCS & PCS was (32.34 ± 25.30) & (41.65 ± 11.82), respectively. Majority (67.6%) had a moderate level of COVID-19 stress. A significant negative relationship between total stress scores and HRQOL domains was observed. Conclusion: Majority subjects had a moderate level of stress related to COVID-19 lockdown. Stress during COVID-19 has a significant negative association with both physical and mental HRQOL in which MCS was significantly lower than PCS. It is recommended to evaluate the effectiveness of stress management program and follow a holistic approach.